Green practice knowledge profiling among the technical and vocational education masters programme students - Lee, Ming Foong; Muhtar, N.S.; Lai, C.S. (IOP Publishing, 2018)
Global warming is utmost problem because of the negative impact to all creatures of the earth. The best solution for this issue should through education. Therefore, this study was conducted to identify the green practice knowledge among the Technical and Vocational Education Masters’ students in Universiti Tun Hussein Onn Malaysia. Green practice knowledge refer to National Green Technology Policy four key areas by KeTTHA which is energy sector, building sector, water and waste water management sector, and transportation sector. A total numbers of 87 students were selected as respondent using stratified sampling technique in this study. A survey method using questionnaire was employed as research design for this study. The gathered data were analyse using sum, mean score, standard deviation, Kruskall Wallis test and Mann Whitney U test. The findings found that the level of green practice knowledge was at the medium level. The findings also shown that there was no significant in the level of green practice knowledge from the aspect of gender and background of study among the respondents. However, there was a significant difference in green practice knowledge among the respondents in terms of age. As a conclusion, the global warming impact can be minimize by increasing the green knowledge, awareness and practising among the communities in their lifestyle.